Measles Enteritis in Gunung Wenang General Hospital Manado - Taufan I. W.; T. H. Rampengan (Paediatrica Indonesiana, 1991)
The incidence and mortality rate of 48 measles enteritis cases has been evaluated retrospectively, during the period of January 1986 to December 1989. Children under 2 years old were 21 cases (43.8%), between 2-5 years old 16 cases (33.3%) and more than 5 years old 11 cases (22.9%). Nutritional status based on the classification of Wellcome Trust Working Party revealed normal33 (68.8%), moderate malnutrition 12 (25%) and severe malnutrition 3 cases (6.3%). Diarrhea and mild dehydration was found in 36 f75%), moderate dehydration 10 (20.83%) and severe dehydration 2 cases (4.2%). Six ( 12.5%) out of 48 cases had had measles vaccination. Twenty jour cases (50%) of measles entent1s had other complications. The mortality rate was 2.1% comprising one pat1ent, who suffered from measles enteritis with severe dehydration bronchopneumonia, enchephalitis and severe malnutrition.